Использование технологии микроплазменного оксидирования для создания нелинейных формирующих линий - Резинкин, Олег Лукьянович (My University, 2010)
Сформульовані вимоги до конструкції та технології виготовлення розподіленої високовольтної формуючої лінії з нелінійним діелектриком. Наведені результати розробки формувача ударних електромагнітних хвиль з активним діелектриком виготовленим за технологією мікродугового покриття.

Engineering and technological requirements for distributed high voltage forming line with nonlinear dielectric have been formulated. Results of design of pulsed electromagnetic shock waves generator with active dielectric produced by spark sintering technology have been described.
Keywords: электромагнитное поле; нелинейный диэлектрик; электромагнитный импульс; диэлектрическая проницаемость; диссипация энергии; активный диэлектрик; высоковольтные импульсные линии